2022
DOI: 10.3171/2021.4.jns204127
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of dexamethasone in the perioperative management of glioma patients

Abstract: OBJECTIVE In this single-institution retrospective cohort study, the authors evaluated the effect of dexamethasone on postoperative complications and overall survival in patients with glioma undergoing resection. METHODS A total of 435 patients who underwent resection of a primary glioma were included in this retrospective cohort study. The inclusion criterion was all patients who underwent resection of a primary glioma at a tertiary medical center between 2014 and 2019. RESULTS The use of both pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
6
2
Order By: Relevance
“…In comparison to previous literature 9,50,51 , this study did not conclude that diabetes and the use of steroids are risk factors for postoperative meningitis. This difference in ndings may be due to the higher rate of corticosteroid usage and the lower number of diabetes patients in our study.…”
Section: Research On Urinary Tract Infections Combined With Meningiti...contrasting
confidence: 99%
“…In comparison to previous literature 9,50,51 , this study did not conclude that diabetes and the use of steroids are risk factors for postoperative meningitis. This difference in ndings may be due to the higher rate of corticosteroid usage and the lower number of diabetes patients in our study.…”
Section: Research On Urinary Tract Infections Combined With Meningiti...contrasting
confidence: 99%
“…Clinical data lately likewise raised the question regarding the safety of DM treatment for symptom control in glioma patients, as in a retrospective analysis, Medikonda et al showed that perioperative dexamethasone use may negatively impact survival in adult glioma patients. This effect was most pronounced in patients receiving only preoperative dexamethasone 20 . Likewise, a meta‐analysis including 2230 adult glioblastoma patients partly confirmed an association of DM application with poor treatment outcome 21 .…”
Section: Discussionmentioning
confidence: 70%
“…This effect was most pronounced in patients receiving only preoperative dexamethasone. 20 Likewise, a meta-analysis including 2230 adult glioblastoma patients partly confirmed an association of DM application with poor treatment outcome. 21 However, there is no significant data derived from pediatric cohorts available to this day.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the DEX-CSDH trial, 5 the risk of any infection in patients receiving dexamethasone was 6.4% compared with 1.1% in the placebo group. Medikonda et al 11 found that the use of pre and postoperative dexamethasone in glioma patients was associated with a trend towards the development of SSIs (3% vs 0% in single or no use, P = 0.082) and worse outcomes. In contrast, in the larger, multicenter PADDI trial, in which 7.4% of participants were neurosurgical cases, dexamethasone use was noninferior to placebo for SSIs within 30 days of surgery 12 .…”
mentioning
confidence: 99%